KEMATANGAN EMOSI DAN PENYESUAIAN PERKAWINAN PADA ISTRI YANG MENIKAH DINI DI KABUPATEN GROBOGAN - Romadhoni, Nofrida Tiar Ayu; Sarajar, Dewita Karema (Prodi Psikologi- Fakultas Psikologi & Humaniora - Universitas Teknologi Sumbawa, 2025)
This study aims to determine the relationship between emotional maturity and marital adjustment among wives who married at an early age in Grobogan Regency. The data analysis method employed in this research is the Pearson correlation test, as the study involves one independent variable and one dependent variable. The correlation was calculated using SPSS version 25. Early marriage is often accompanied by various challenges, both emotionally and in the dynamics of the marital relationship, which can affect the quality of marital adjustment. This research uses a quantitative approach with a survey method, involving wives who were married under the age of 20 as respondents. The instruments used in the study include an emotional maturity scale and a marital adjustment scale. The results of the data analysis show a significant relationship between emotional maturity and marital adjustment. The higher the level of emotional maturity, the better the adjustment within the household. These findings underscore the importance of emotional readiness in facing marriage, particularly for women who marry at a young age.